A comparative study of object detection models for Real Time Application in Surveillance Systems - Alam, Saimun; Ahmed, Mahim Uddin; Hasan, Mehedi; Islam, Md. Morshedul; Arnob, Shahed Mehrab (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.